Ibn Amira al-Makhzoumi The judge and writer of Bejaia as an aspect of cultural contact between.the Middle Maghreb and Andalusia)AH / 1186 - 1260 (مجلة إحالات, 2026)
The Maghreb was one of the most important geographical gates for arrivals from Andalusiaas a passage towards the rest of the world.The importance of this site has increased through the two kingdoms that rose up on its land, and it became a political rule in which there is great competition between two cities thatembraced the chairs of government, science and literature. And the knowledge, literature andpolitical ability with him, and this is what happened with the famous Andalusian writer Ibn Amira Al Makhzoumi.